PENERAPAN TERAPI MUSIK LULLABY UNTUK MENAIKKAN BERAT BADAN BAYI DENGAN BBLR DI RUANG PERINATOLOGI: STUDI KASUS - Luthfiati, Nur; Sulistyawati, Ririn Afrian; Intani, Merlisa Kesuma (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Low Birth Weight (LBW) infants are at risk of experiencing growth and developmental disorders as well as health complications. One of the non-pharmacological approaches to improve the weight of LBW infants is lullaby music therapy, which consists of soft and rhythmic music believed to have a calming effect, stimulate the sucking reflex, and improve the quality of the infant’s sleep. This study aimed to explore the effectiveness of lullaby music therapy as a non-pharmacological intervention in increasing the weight of LBW infants. The intervention was carried out by playing lullaby music for 20–30 minutes, 2–3 times per day, for three consecutive days. The results showed that lullaby music therapy administered for three consecutive days led to changes in the infants’ weight. During the first two days, there was a decrease in weight; however, on the third day, an increase was observed. Lullaby music therapy also had positive effects on improving the sucking reflex and stabilizing the infants’ physiological parameters. These findings indicate that lullaby music contributes to enhancing feeding processes and nutritional intake, which ultimately support weight gain in LBW infants. The conclusion of this study is that lullaby music therapy is effective in supporting weight gain, improving the sucking reflex, and maintaining physiological stability in LBW infants. This therapy may be considered a non-pharmacological intervention in neonatal nursing; however, further research with larger sample sizes is needed to strengthen its scientific basis.